Civil Service Reform in the States - J. Edward Kellough , Lloyd G. Nigro (State University of New York Press, 2009)
Government jurisdictions in the United States have frequently reformed their administrative systems as they have struggled with changing political and economic circumstances. These administra- tive reforms are typically designed to reflect popular new models or emerging paradigms for public management. They are driven by complex and not necessarily congruent combinations of values and purposes ranging from the purely partisan to the largely technical. During the twentieth century, for example, there were at least twelve highly visible efforts to reform federal administrative arrange- ments—about one every eight years.1 There were also innumerable similar reforms enacted by state and local governments. With each reform, changes, both large and small, in the administrative machin- ery of government are implemented, and the effects of those changes often last long after the reform itself has become a distant memory. It is interesting to observe that, more often than not, public person- nel or civil service systems are at the top of the reform agenda. The fact that personnel policy is the frequent target of reform bears witness to the central importance of personnel management to technically and politically effective government operations. It is through the personnel function that public agencies recruit, select, develop, pay, and hopefully retain highly qualified employees. These civil servants, in turn, directly influence the content and execution of public policies. They are the individuals responsible for translating objectives contained in legislative enactments or executive orders into the daily operations of government programs. Since the 1960s, as important new issues have arisen to demand the attention of pub- lic personnel managers and the constituencies they serve, the scope and impact of the public personnel function have grown and become even more socially and politically critical. Equal employment oppor- tunity, pay equity concerns, labor relations, and constitutional pro- tections are but a few of the issues now central to the field.2 As a result, public personnel policy and management are increasingly dynamic and complex, and it is always the case that the technical, ethical, and political aspects of the civil service attract attention.